Gingival Curettage Treatment in Chronic Periodontitis Patients: A Case Report - Rahmi Sania Yuliani; Sulistiawati; Ifadah (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: Periodontitis is defined as an inflammatory disease of the tooth-supporting tissues caused by certain microorganisms. One of the surgical treatments for generalized chronic periodontitis is gingival curettage. Gingival curettage is a closed surgical procedure involving the removal of inflamed soft tissue lateral to the pocket wall. The goal is to promote the attachment of new connective tissue to the root surface by removing the pocket lining and junctional epithelium using a curette.Purpose: To determine whether gingival curettage is an effective treatment for patients with generalized chronic periodontitis. Case presentation: A 26-year-old female patient presented to the Special Dental and Oral Hospital of South Sumatra Province with complaints of rough masses on all of her teeth. Clinical examination revealed calculus in all regions, an OHI-S score of 1.83 (medium), and an O'Leary plaque index score of 41.37%. Probing depths ranged from 1 to 5 mm, with positive BOP on almost all teeth. After scaling and root planing, the decision was made to proceed with gingival curettage for the patient.Conclusion: In this case, gingival curettage helped reduce pocket depth and restored the gingiva to a more normal appearance. This demonstrates that gingival curettage can be an effective treatment for chronic periodontitis.